Stakeholder participation in adaptation to climate change. Lessons and experience from Germany. - (:unkn) unknown (My University, 2013)
Offenheit und Kooperation sind zentrale Grundsätze der Deutschen Anpassungsstrategie, weshalb die Entwicklung und Umsetzung von Anpassungspolitik durch einen intensiven Prozess der Stakeholderpartizipation begleitet wird. Insbesondere drei Bundesministerien haben diesen Partizipationsprozess gestaltet: das Umweltministerium, das die Federführung für das Thema Anpassung innehat, das Forschungsministerium durch die Förderung zweier Forschungsprogramme zu Anpassung und das Bau- und Verkehrsministerium durch die Unterstützung von Modellprojekten. Eine Analyse dieser Beteiligungsprozesse zeigt, dass unterschiedliche Grade der Beteiligung erreicht wurden (Kommunikation, Konsultation, Co-Produktion und Mitentscheidung) und dass sowohl wissenschaftsorientierte als auch politikorientierte Ansätze verfolgt wurden. Der Bericht gibt Empfehlungen zur Gestaltung von partizipativen Prozessen und schlägt in Abhängigkeit von den verfolgten Zielen geeignete Ansätze und Methoden vor.

Openness and cooperation is one major principle of the German Adaptation Strategy; the development and implementation of adaptation policies is hence accompanied by broad and diversified stakeholder participation processes. Mainly three German ministries have initiated and supported stakeholder participation: the Federal Ministry for the Environment that has the lead in developing adaptation policies, the Federal Ministry for Education and Research through funding two research programs on adaptation, and the Federal Ministry of Transport, Building and Urban Development through funding regional model projects. A review of these stakeholder integration processes shows that different degrees of participation were realised (communication, consultation, co-production and co-decision) and that both science-based and policy-based approaches were pursued. While science-based approaches aim at improving research results, policy-based approaches target at influencing political decision-making. A broad variety of actors have been involved and almost all 15 sectors mentioned in the German Adaptation Strategy have been covered. While topics such as agriculture or water have been broadly addressed, economic issues have been touched only by a minority of events. Researchers and representatives from administration have participated in almost all events whereas policy-makers, companies and civil society organizations were less represented. The report concludes with recommendations for planning and conducting stakeholder participation processes and suggests suitable designs depending on the pursued objectives.
Keywords: Umweltpolitik; Klima; Kooperation; Partizipation; Klimaschutz; Klimapolitik